Development of diazonium functionalized electrochemical aptasensor for simultaneous detection of tuberculosis antigens - Yunus, Muhammad Hafiznur (2023)
In the management of tuberculosis (TB), prompt and accurate diagnosis is of the utmost significance for the purpose of life-saving and transmission cessation. Despite being time-consuming and having a low sensitivity, traditional smear microscopy and culture procedures remain the mainstay of TB antigen detection modality. To overcome this limitation, this study highlights the fabrication of the first amperometric dual aptasensor for the simultaneous detection of Mycobacterium tuberculosis CFP10 and MPT64- secreted antigens to facilitate better TB diagnosis and control. The proposed sensor utilized the aptamer–antibody sandwich assay that would be measured by chronoamperometry via electrocatalytic reaction between peroxidase-conjugated antibodies, hydrogen peroxide (H2O2), and hydroquinone (HQ). The aptamer-target binding ability for CFP10 and MPT64 was first reassessed using enzyme-linked oligonucleotide assay (ELONA), which showed a statistically significant difference between the wells incubated with the target antigen compared to other control well with a p-value <0.0001, indicating the sensitive and selective behavior of the selected aptamer towards the target antigen. The aptamers were then immobilized via carbodiimide covalent chemistry over the disposable screen-printed carbon electrodes (SPCE) modified with 4-carboxyphenyl diazonium salt. The successful deposition of the diazonium layer was verified with several methods, including X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared (FTIR), contact angle, and electrochemical analysis, i.e., cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Analysis of the diazonium-modified surface by FTIR showed a new sharp band at ~1703 cm–1 attributed to the C=O stretching of the terminal carboxylic groups that was absent in the bare SPCE surface. Additionally, the appearance of moderate peak intensity at ~1255 cm–1 and ~1367 cm–1 contributed to the C–O stretching and O–H band, respectively, confirming the existence of the 4-carboxyphenyl diazonium salt on the carbon surface. For the XPS analysis, there was a significant increase in the oxygen content from 4.85% (bare) to 18.81% (diazonium-grafted), suggesting the surface enrichment with oxygen corresponding to the oxygen belonging to the carboxylic functionality of the 4-carboxyphenyl diazonium. Further high-resolution scan of C 1s components also produced a unique peak around 289.5 eV assigned to the carboxylic group, H–O–C=O. This peak is a typical signature of a surface modified with carboxylic functionality. CFP10 and MPT64 single aptasensors were initially fabricated and optimized to validate their analytical and diagnostic performance before being adapted to the dual detection platform. The stepwise assembly was characterized using CV and EIS techniques. Under optimal conditions, the CFP10 single aptasensor exhibited a linear relationship with the increasing CFP10 antigen concentration of 5 to 500 ng mL–1. The detection (LOD) and quantification limit (LOQ) of the single CFP10 aptasensor was estimated to be 1.22 ng mL–1 and 1.93 ng mL–1, respectively. The MPT64 single aptasensor, on the other hand, achieved a LOD and LOQ of 1.11 ng mL–1 and 1.402 ng mL–1, respectively, with an increasing trend in the current response with the increase in antigen concentrations from 5 to 200 ng mL–1. Both single aptasensors also showed excellent current reproducibility with a relative standard deviation (RSD) of 1.39% (CFP10) and 1.52% (MPT64) when testing with a series of five modified electrodes under the same preparation batch. The CFP10 single aptasensor demonstrated good storage stability without significant current difference for up to two months when stored at 4°C under a dry environment. Meanwhile, the MPT64 aptasensor displayed slight attenuation by 8% from the initial current (day 0) after day 45 of storage. Clinical evaluation using TB-positive [TB (+)] and non-TB sputum samples [TB (–)] revealed satisfactory results for every aptasensor. Surprisingly, the diagnostic sensitivity and specificity between both sensors were found to complement each other, thus making them ideal candidates to be combined on a dual simultaneous detection platform. The CFP10 single aptasensor produced 100% sensitivity and 81.8% specificity, while MPT64 single aptasensor achieved 88% and 100% for diagnostic sensitivity and specificity, respectively. Furthermore, exceptional analytical performances were obtained upon applying both detections on a dual SPCE, as demonstrated by the detection limit of 1.62 ng mL–1 (CFP10) and 1.82 ng mL–1 (MPT64) with no significant reaction when incubated with other non-target reagents. A linear dependence of the amperometric signal was observed between the corresponding target antigens concentration in the range of 0.5 to 100 ng mL-1 and 0.75 to 250 ng mL–1 for CFP10 and MPT64, respectively. An RSD value of 2.6% and 2.99% for CFP10 and MPT64 working electrodes suggested a reliable performance of the fabricated when tested with the amperometric technique. The dual aptasensor also demonstrated good storage stability for up to 35 days at 4°C. In the clinical study, the MPT64 working sensor was the least sensitive (91.7%), followed by the CFP10 working electrode (95.8%). Overall, a combined CFP10 and MPT64 detection achieved a perfect score for TB diagnosis when evaluated on 24 TB (+) and 13 TB (–) sputum samples, thus indicating the readiness of the developed assay to be used clinically. In conclusion, the developed CFP10-MPT64 dual electrochemical aptasensor is a potentially sensitive, specific, and easy-to-apply assay for TB. Therefore, it would be a promising alternative to conventional microscopy and TB culture.